La música como recurso didáctico en el proceso de enseñanza-aprendizaje de los niños y niñas del 2do inicial a, b, c, de la escuela de educación general básica “18 de Noviembre” de la ciudad de Loja, periodo 2018-2019 - Albán Ontaneda, Angie Belén (2020)
The integration of the music to the development of the children classes in their first educational years, provide many benefits such as the development of sensitivity (musical and emotional), fine and gross motor skills, diction, memory, attention and concentration, logical thinking, socialization, facility to learn arithmetic and numbers, facility to learn languages, coordination, and expression. The main goal of the study was to demonstrate the music importance as a teaching resource and its effect in the teaching-learning process of children of second initial level to use the music daily in the child education. Also, to identify how the second level educators of the school "18 de Noviembre" uses the music to give classes. In this investigation, a study was carried out taking as a population the authorities of the principal and assistant principal educational establishment, as well as six teachers who work with the children of the second initial levels. The purpose of the following investigation was studying the importance of music as a teaching resource and its effect in the teaching-learning process of the second initial level with the purpose of applying music in the children's education. The instruments used to gather information were observation to the six teachers of the second initial level (A, B, C, D, E, and F) in how they teach classes, the interviews applied to the authorities and three of the teachers of second initial level. Also, the surveys applied to the six teachers of the second initial level supported with multiple-choice questions. The results allowed to obtain conclusions for instance lack of music knowledge as a teaching resource, the music teaching resources are scarce, there are not musical teaching guides, there are not teacher training workshops focused on music as a teaching resource for the teaching-learning process. Therefore from these conclusions could be carried out as an alternative proposal based on the elaboration of a didactic guide of musical activities focusing on the aims of artistic expression in the second level which proposes the initial level curriculum of Ecuador. The methodology used for this investigation was scientific and analytical in terms of the theory studied and hermeneutic since it was made the respective treatment to the results obtained from the investigation. According to the analysis of the results obtained through the instruments used with the educators, the conclusion was reached that all the educators examined make low use of music as a teaching resource for the teaching-learning process in the classroom.